Kajian KAJIAN USAHA BARU ASPEK PEMASARAN, PRODUKSI, KEUANGAN, DAN MAKRO EKONOMI : (STUDI DAN SURVEY PADA PDAM TIRTAMARTA YOGYAKARTA) - Kuswantoro, Ferri; Dwiwinarno , Titop; Hasthoro , Handoko; Hasanah, Erni; Nurwiyanta, Nurwiyanta; Burhanudin, Burhanudin; Lokananta, Robid; Mardianto, Toni (MEDIA RISET EKONOMI [MR.EKO], 2023)
ABSTRACT Along with the increasing need for mineral water, regional company Tirtamarta Yogyakarta will make a break through by developing diversification of products branded "Ayo". Hence the aim of the conducted study was to conduct a feasibility research of the â€œAyoâ€ manufacturer from the marketing, production, financial, and macroeconomic aspects. With the efficient and effective production setting endorsed by the high need of marketing relations in mineral water and the capability in existing innovative manufacturing machineries, the financial research was shown to be feasible. It was indicated the payback period was faster than the target investment period, the net present value (NPV) generated was positive, the benefit cost ratio (BCR) was greater than 1 (one), and the internal rate of return (IRR) placed in the range 14% was greater than the discount factor (DF) used, namely 12%. In the macro-economic aspect, there are supportive government policies, transportation and communication infrastructures as well as high purchasing power of the people. Thus the business feasibility study of the brand "Ayo" Tirtamarta Yogyakarta as a whole was stated to be feasible to operate. Keywords : New Business, Aspects, Marketing, Production, Finance, And Macroeconomics